Land Readjustment Model for Transit-Oriented Development (TOD) Projects: Generating Optimal Financial Benefits - Gunawan Saroji; M. Ali Berawi; Dillan Satyagama; Mustika Sari; Roy Woodhead (Salehan Institute of Higher Education, 2023)
Transit-Oriented Development (TOD) projects are increasingly recognized as vital components of sustainable urban planning, aiming to create compact, walkable, and mixed-use communities centered around high-quality public transportation systems. However, implementing TOD projects poses significant challenges, especially in land acquisition and redistribution. This research addresses these issues in the context of the MRT Jakarta project and proposes a land readjustment approach as a potential solution. The study combined qualitative and quantitative methods to compare existing and ideal land use in the TOD area and benchmark successful TOD models from different countries. A comprehensive financial analysis was performed to assess the potential financial impacts of the proposed model. The analysis reveals differences between the existing land use in the Fatmawati TOD area and the ideal TOD model, suggesting the need for adjustments to achieve better land use diversity and economic vibrancy. The financial analysis demonstrates positive feasibility for the TOD project, surpassing the minimum attractive rate of return (MARR) threshold. However, the potential value of the reserved area covers only 16% of the total land readjustment (LR) costs, indicating the necessity for further measures to enhance financial feasibility. The study proposes leveraging existing apartment buildings as temporary relocation sites, optimizing resources, and increasing overall financial viability to address substantial relocation costs. Exploring different property redistribution scenarios reveals the importance of balancing landowners' benefits with the developer's financial feasibility for a successful TOD project. Overall, this research provides valuable insights and a comprehensive framework for implementing thriving and sustainable transit-oriented communities in Jakarta. Further research and collaboration among stakeholders are essential to refine the proposed model and ensure successful TOD project implementation in the future. Doi: 10.28991/CEJ-2023-09-10-012 Full Text: PDF